A Study on the Knowledge, Attitude, and Practices of Iranian Mothers towards Childhood Obesity - Karimy, Mahmood (Obes Facts, 2019)
OBJECTIVES: In the recent decades, a dramatic increase in childhood obesity is one of the main public health problems. The aim of the study was to assess the knowledge, attitude, and practices (KAP) of Iranian mothers towards childhood obesity. METHODS: This cross-sectional descriptive research was conducted on KAP of 432 mothers and their children aged 6–7 years (214 boys and 218 girls) who were referred to the Zarandieh health centers, Iran, in 2017. The participants were selected via multistage random sampling. Demographic and KAP data were obtained by self-report using standard questionnaires. The weight and height of the subjects were measured according to standard methods and body mass index was calculated. Data were analyzed by inferential statistics using SPSS18 software. RESULTS: The prevalence of obesity (OB) was 11.5% in boys and 7% in girls. The mean score for attitude for mothers with normal-weight children was higher than for mothers with obese children. Food habits like consumption of breakfast, having fast food at least twice a week, and eating in front of TV were associated with OB. Physical activity habits like duration of TV watching/computer games/sleep and regular physical exercise were associated with OB. CONCLUSIONS: This study identified the importance of educating Iranian mothers to change of lifestyle (eating and physical activity habits) and attitudes towards weight control in their children. Therefore, it seems that these results may be valuable in the development of educational programs and strategies for the prevention of childhood obesity.